Enhancing Performance and Work Ethics of Low-Educated Employees - Rudang Irene Celica; Andika Putra Pratama (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This research examines strategies to enhance the performance and work ethics of employees with limited educational backgrounds by implementing business ethics and organizational development practices, with a focus on PT Medi Modular Luar Biasa (PT MMLB), an Indonesian healthcare infrastructure company. The research addresses the challenges faced by companies in managing low-educated employees, including cognitive limitations, communication barriers, and difficulties adapting to organisational changes, which often lead to suboptimal performance and ethical lapses. Through qualitative interviews with employees and management, the study reveals significant differences in how employees with varying educational backgrounds understand and implement corporate values such as integrity, and professionalism. The research highlights the need for ethical leadership and structured organisational support to address these challenges. The findings suggest that enhancing the ethical climate and providing tailored training are crucial for improving both performance and work ethics among low-educated employees. The study proposes interventions such as clarifying role expectations, reinforcing ethical guidelines, and fostering a supportive work environment to drive continuous improvement and employee well-being. The research contributes practical recommendations for businesses facing similar challenges, emphasising the importance of ethical leadership in shaping positive employee behaviour and organisational outcomes.